KETAATAN PELAJAR SMU TERHADAP ATURAN PELARANGAN MINUMAN KERAS DI WILAYAH POLSEK JAKARTA BARAT - crestella vallery (Ilmu Hukum Prima (IHP), 2019)
In teenager’s period children experience puberty. Teenagers tend to be unstable, emotional and have a big curiosity. A great curiosity in a child is sometimes not developed or use for positive things but instead to negative things, one of it is consuming liquor. It makes consumers drunk and unconscious. Moreover in Indonesia there is a regulation that teenagers under 21 years old are not permitted to consume alcoholic beverages but there are still many teenagers who consume alcohol. On this occasion the author will discuss the opinions or responses of citizens regarding the effectiveness of liquor laws for teenagers under age of 21 years. Based on the survey results, the authors learned that the public considered the government is not strict about the regulations on teenagers under the age of 21 that consume liquor due to lack of tightening and implementing the rules. In addition, it is also due to the lack of supervision of ID cards or identity cards and liquor easily available at low prices. Thus, it can be said that according to the citizens the legal effectiveness of the prohibition of teenagers under the age of 21 is still not effective and has not been implemented properly.